A framework for promoting behavioral change through game design elements in social marketing - Paulo Henrique Serrano; Nelsio Abreu (Gestão e Desenvolvimento)
This paper presents a conceptual and practical framework designed to integrate game design elements into social marketing practices, aiming to enhance user engagement and intrinsic motivation. Addressing a gap in existing generalist models, the proposed framework is grounded in the principles of Transformative Consumer Research (TCR) and the Capability Approach, providing a targeted solution for promoting pro-social behaviors. The framework, titled LOP (Listen, Observe, Play), is structured around six key stages: activating pre-existing knowledge, characterizing players, recognizing the environment, identifying variables, implementing game design elements, and testing and evaluating indicators. Initial insights from exploratory application indicate that the framework may have potential to enhance user engagement and support behavior change, while also highlighting challenges in scaling and adapting it to diverse technological environments. Despite these limitations, the framework offers a promising methodological tool for practitioners and researchers interested in designing interventions that are contextually meaningful and aligned with individuals’ values and capabilities. Future research should focus on the validation of the model across diverse populations and social contexts to refine its applicability and broaden its impact. By aligning theoretical foundations with practical application, this framework contributes to the advancement of social marketing strategies that harness the motivational potential of game design to drive positive change.